A Strategic Social Media Approach to Enhance Brand Recognition in A University Dental Hospital - Hanifah Salma Rosa; Endang Ruswanti; Rokiah Kusumapradja (International Journal of Nursing and Health Services (IJNHS), 2026)
Background: The brand awareness level of the Dental and Oral Teaching Hospital (RSGM-P) at University X remains low, as indicated by the predominance of patients referred by student initiatives (90%) and limited walk-in visits (10%). This may result from the underutilization of social media, low customer engagement, and insufficient electronic word of mouth (eWOM). Objective: This study aims to analyze the effects of social media activities and customer engagement on brand awareness, with eWOM as a mediating variable. Method: A quantitative approach with a cross-sectional design was employed, involving 205 non-student Instagram followers of RSGM-P. Data were analyzed using Structural Equation Modeling (SEM) via LISREL. Results: The findings reveal that social media activity and eWOM significantly influence brand awareness, while customer engagement has no direct effect. However, customer engagement positively influences eWOM, which in turn mediates its effect on brand awareness. Managerial implications emphasize the need for enhanced content strategies, influencer collaboration, and online reputation management. Recommendation: It is recommended that RSGM-P optimize SEO-friendly educational content, strengthen user interactions, and encourage patient reviews as part of brand trust-building efforts. Recomendation: This study contributes to the strategic understanding of digital media utilization in marketing for university-based hospitals